Assessing combining abilities, genomic data, and genotype × environment interactions to predict hybrid grain sorghum performance. Issue 3 (9th August 2021) - Fonseca, Jales M. O.; Klein, Patricia E.; Crossa, Jose; Pacheco, Angela; Perez‐Rodriguez, Paulino; Ramasamy, Perumal; Klein, Robert; Rooney, William L
Abstract: Genomic selection in maize ( Zea mays L.) has been one factor that has increased the rate of genetic gain when compared with other cereals. However, the technological foundations in maize also exist in other cereal crops that would allow prediction of hybrid performance based on general (GCA) and specific (SCA) combining abilities applied through genomic‐enabled prediction models. Further, the incorporation of genotype × environment (G × E) interaction effects present an opportunity to deploy hybrids to targeted environments. To test these concepts, a factorial mating design of elite yet divergent grain sorghum lines generated hybrids for evaluation. Inbred parents were genotyped, and markers were used to assess population structure and develop the genomic relationship matrix (GRM). Grain yield, height, and days to anthesis were collected for hybrids in replicated trials, and best linear unbiased estimates were used to train classical GCA‐SCA–based and genomic (GB) models under a hierarchical Bayesian framework. To incorporate population structure, GB was fitted using the GRM of both parents and hybrids. For GB models, G × E interaction effects were included by the Hadamard product between GRM and environments. A leave‐one‐out cross‐validation scheme was used to study the prediction capacity of models. Classical and genomic models effectively predicted hybrid performance and prediction accuracy increased by including genomic data. Genomic models effectively partitioned the variation due to GCA, SCA, and their interaction with the environment. A strategy to implement genomic selection for hybrid sorghum [ Sorghum bicolor (L.) Moench] breeding is presented herein. Core Ideas: Genomic and classical GCA‐SCA–based models can predict agronomic traits in sorghum hybrids. Genomic models that include G × E effects can increase the prediction accuracy of sorghum hybrids. Genomic models can incorporate the natural population structure existent in hybrid crops. Hybrids adapted to a target environment provide better predictions than non‐adapted hybrids.